Construction of evaluation index system for online medical teaching resources - WANG Jun, ZHANG Kun, ZHANG Shu-hua, DENG Ming-jun, ZHANG Hua (Jichu yixue yu linchuang, 2022)
Online teaching is an effective supplement to traditional teaching. Especially under the influence of from pandemic COVID-19,online education has played an indispensable and important role. However, with the fast development of teaching resources, there is a need for building of standards and norms, quality of resource construction and the outcome evaluation of technology application in online education.This article tries to analyze the deficiencies of performance evaluation in the construction of medical online teaching resources, establish a reasonable evaluation framework, formulate different resource evaluation systems combined with qualitative and quantitative analysis and to introduce theories such as Deming Cycle, and to establish a long-term dynamic evaluation mechanism in order to implement effective evaluation of medical online teaching resources, therefore to guide the optimization of online teaching resources unitilizaion, promote the application of smart technology and thus improve the learning outcomes of education.